Carbon Material Hybrid Construction on an Aptasensor for Monitoring Surgical Tumors - Renyuan Ma; Subash C. B. Gopinath; Thangavel Lakshmipriya; Yeng Chen (Journal of Analytical Methods in Chemistry)
Carcinoembryonic antigen (CEA) is a glycoprotein, one of the common tumor biomarkers, found at low levels in body fluids. Generally, overexpression of CEA is found in various cancers, including ovarian, breast, lung, colorectal, gastric, and pancreatic cancers. Since CEA is an important tumor biomarker, the quantification of CEA is helpful for diagnosing cancer, monitoring tumor progression, and the follow-up treatment. This research develops a highly sensitive sandwich aptasensor for CEA identification on an interdigitated electrode sensor. Carbon-based material was used to attach a higher anti-CEA capture aptamer onto the sensor surface through a chemical linker, and then, CEA was quantified by the aptamer. Furthermore, CEA-spiked serum was tested by using the immobilized aptamer, which was found to not affect the target validation. The limit of detection for CEA in PBS and serum is calculated from a linear regression graph to be 0.5 ng/mL with R2 values of 0.9593 and 0.9657, respectively, over a linear range from 0.5 to 500 ng/mL. This CEA quantification by the aptasensor can help diagnose various surgical tumors and monitor their progression.